THE EFFECTIVENESS OF COLORED PICTURES AND STORYTELLING TECHNIQUES IN TEACHING VOCABULARY TO THE THIRD GRADERS OF ELEMENTARY SCHOOL - Koeswito, Edy (Journal of English Department WM, 2013)
In learning English, it is necessary for learners to possess a large number of words in order to construct proper sentences. Vocabulary has been one of the most important components to master. Introducing vocabulary would be better done as early as possible as it is possible and easy for kids to absorb fresh material given by teachers. In teaching vocabulary to young learners, there are various techniques which can be used. Two of them are colored pictures and storytelling techniques. Teaching vocabulary using storytelling can make learning experiences more realistic or dynamic to children. Besides, using colored pictures technique can ease the children to remember words by recognizing details, shapes, sizes, and colors. Therefore, this study is conducted in order to know the effectiveness of colored pictures and storytelling techniques in teaching vocabulary to the third graders of elementary school.